Rancang bangun pabrik pellet dari plastik reklaim - Suraswati, Agustin; Pramono, Pramono (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1999)
The purpose of this design is to find out process of production and the relation between cost, sell price and percentage of break event point. Production of capacity planned is 975 kg per day, so that in one a year with 288 work day the capacity produced is 280.800 kg of pellet. The economical calculation are as follows = the total capital + working capital = Rp. 272.543.806,00, the total production cost is variable cost a year + fixed cost a year = Rp. 306.122.244,00, the manufacturing cost = Rp. 1.090,18/kg, the profit calculation before taxing is Rp. 58.917.756,00, after taxing is Rp. 31.902.205,00, the pay out period calculation consist of the percentage of profit to return the capital (rate of return) before taxing is 21,62%, after taxing is 11,71%, and they pay out period before taxing 3 year 1 mounth, after taxing is 5 year 6 mounth; the break even calculation consist of the break even point is Rp. 242.190.990,00, the percentage of break event point is 66,35% and the capacity of break event point is 186 ton pllet. INTISARI Rancang bangun ini bertujuan untuk mengetahui proses produko dan hubungan antara biaya, harga jual dan presentase batas rugi laba. Lapasitas produksi yang direncanakan sebesar 975 kg pllet per hari, sehingga dalam 1 tahun dengan 288 hari kerja, kapasitas yang dihasilkan 280.800 kg pellet plastik reklaim. Dalam perhitungan analisisa ekonomi diperoleh hasil sebagai berikut = total modal yang terdiri dari tetap dan modal kerja = Rp. 272,543,806,00, biaya produksi yang terdiri dari biaya tidak tetap 1 tahun dan biaya tetap tahun = Rp. 306.122.244.00, Harga pokok produksi = Rp. 1.090,18/kg. Keuntungan = sebelum pajak Rp. 58.917.756,00 dan sesudah pajak = Rp. 31.902.205,00, keuntungan pengembalian modal sebelum pajak 21,62% dan sesudah pajak 11,71%, serta waktu pengembalian modal sebelum pajak 3 tahun 7 bulan dan sesudah pajak 5 tahun 6 bulan. Perhitungan nilai batas rugi laba = 66,35% dan kapasitas batas rugi laba = 186 ton pellet.